2018
DOI: 10.1111/tid.12923
|View full text |Cite
|
Sign up to set email alerts
|

Does the urinary tract infection caused by carbapenem‐resistant Gram‐negative bacilli impact the outcome of kidney transplant recipients?

Abstract: The incidence of urinary tract infection (UTI) after kidney transplantation (KT) caused by multidrug-resistant (MDR) bacteria is growing. The aim of this study was to analyze the impact of UTI caused by carbapenem-resistant Gram-negative bacteria (CR-GNB) in the survival of graft and recipients following KT. This was a retrospective cohort study involving patients who underwent KT between 2013 and 2016. Patients were followed since the day of the KT until loss of graft, death or end of the follow-up period (31… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 36 publications
0
11
0
1
Order By: Relevance
“…Regarding risk factors associated with MDR bacterial infection, female, older age and diabetes mellitus were prevalent independent risk factors associated MDR bacterial infection. 1 , 43 , 44 In our survey, we proved that female gender was a risk factor for MDR bacterial infection while no relationship has been found either with diabetes mellitus or older age. This may due to the small number of diabetes mellitus recipients and patients over 60 years old rarely receive kidney transplant surgery in China.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…Regarding risk factors associated with MDR bacterial infection, female, older age and diabetes mellitus were prevalent independent risk factors associated MDR bacterial infection. 1 , 43 , 44 In our survey, we proved that female gender was a risk factor for MDR bacterial infection while no relationship has been found either with diabetes mellitus or older age. This may due to the small number of diabetes mellitus recipients and patients over 60 years old rarely receive kidney transplant surgery in China.…”
Section: Discussionmentioning
confidence: 59%
“…Kidney transplantation (KT), as the only curable option of treatment for chronic kidney disease, is threatened by all kinds of infections since they can pose a risk of acute rejection, delayed graft function, endanger allograft and patients’ survival, and result in longer hospital duration. 1–4 Moreover, they accounts for approximately 18% to 23% of death after KT. 5 The vast majority of infections occur within 6 months after surgery, especially within the first month.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Lübbert et al reported higher infection rates and excess mortality among patients admitted to the liver transplant unit during a CP-Kp outbreak in a German hospital [22]. In a large Brazilian cohort of over a thousand kidney transplant recipients, 2.1% of the patients had CP-Kp infections, which were associated with a BSI in 38.7% of the cases, including a significantly reduced survival rate and an association with a higher SOFA score at the time of diagnosis [23].…”
Section: Discussionmentioning
confidence: 99%
“…IC 95%: 1,3-3,2, p: 0,001]; Ariza-Heredia y cols., 20 no encontraron diferencia significativa en la tasa de filtración glomerular estimada ni en el valor absoluto de creatinina sérica en receptores de TxR con ITU (p: 0,646), sin embargo, en la estimación de la tasa de filtración glomerular con iotalamato encontraron una reducción de 5,09% en pacientes receptores de TxR que sufrieron al menos un episodio de ITU (p: 0,044); Sing y cols., 21 no encontraron diferencia en la función renal de receptores de TxR con ITU (p: 0,38) ni en la proteinuria (p: 0,14) tras un mes de ocurrido el evento infeccioso; Pesce y cols 3 recientemente describieron la ITU recurrente como factor predictor independiente de la función del injerto renal [HR: 2,2. IC 95%: 1,3-3,5, p: 0,001] y por último, Pinheiro y cols 22 definieron a la ITU causada por gérmenes productores de carbapenemasas como factor asociado a aumento de la mortalidad del receptor de TxR (HR: 2,62, IC 95%: 1,37-5,00, p: 0,04) y a la disminución de la supervivencia del injerto renal (p:0,006).…”
Section: Discussionunclassified